Development of Character Education Based on Tri Hita Karana with a Contextual Approach in Accounting Education: A Literature Review - Chandra Dirciana Ximenes Da Costa; Ni Luh Putu Uttari Premananda; Ni Putu Eka Ariningsih; Komang Rika Trisnayanti (Samā Jiva Jnānam (International Journal of Social Studies), 2024)
The prevalence of unethical practices and the erosion of ethical values in the accounting profession underscore the need for integrating character education into accounting curricula. High-profile accounting scandals like Enron and WorldCom highlight the critical importance of fostering ethical behavior and social responsibility among future professionals. This literature review explores the integration of Tri Hita Karana, a Balinese philosophy promoting harmony among human-God, human-human, and human-environment relationships, with contextual learning in accounting education. The study suggests that incorporating Tri Hita Karana into the curriculum through community-based projects and real-world ethical scenarios enhances students' ethical and professional competencies. Empirical evidence from various studies supports the effectiveness of this integrated approach in developing students' ethical judgment, social and environmental awareness, and spiritual well-being. This holistic educational model not only prepares students for professional challenges but also promotes broader cultural shifts towards ethical integrity in professional practices.